3D involute gear evaluation – Part I: Workpiece coordinates. (February 2019) - Härtig, Frank; Stein, Martin
Highlights: A novel involute gear coordinate system is introduced. General definitions and mathematical calculation methods are provided. They allow 3D coordinates to be evaluated in conventional evaluation cross sections. The definitions and formulas presented complete existing standards and guidelines. They provide clear instructions required for handling a gear as a full 3D object. Abstract: The definition of 3D workpiece coordinates for cylindrical involute gears, together with their formal relation to conventional cross sections, are prerequisites for an unambiguous and thus reliable evaluation of 3D measurement data. Both will be described in this article, as no corresponding information is currently available in national or international standards and guidelines. The definitions and calculation methods presented here are part of reference algorithms used by the Physikalisch-Technische Bundesanstalt (PTB), the national metrology institute of Germany, to certify gear evaluation software.